Bandar Tembakau Madura” Patron-Client Relationship and Social Transformation in the Tobacco Trade Organization in Madura: Bandar Tembakau Madura” Patron-Client Relationship and Social Transformation in the Tobacco Trade Organization in Madura - latif kusairi (University of Muhammadiyah Malang, 2022)
This article studied about social transformation and its complexity experienced by various classifications of traders in the tobacco world in Madura. Tobacco for Madura's society even though it's only seasonal, and in the last few years the price was very irregular and unpredictable - sometimes it's good fallen, however tobacco being the important economic factor in the trades and agriculture of Madura's tobacco, this article observed more about the social networks among the offenders through library research. The finding was in the world of tobacco's trade-in Madura, the important role that connects the tobacco plantation of Madura's inhabitants with the factory side were the tauke, juragan (skipper), and bandol.Tauke represented the large factories who yet they swayed and led away by Chinese ethnic origin, while the skipper and bandol more taking role as 'broker' with various segmentation. In the trading practice carried out, there was a relational pattern that was built, both between tauke with juragan (skipper) or between juragan (skipper) with bandol (retailer). Both these relational patterns have the element which more or less the same although in different levels. The skipper was highly dependent on assets owned by tauke, where the tauke use the assets to give to bandol as assets also in buying the tobacco from the farmers directly as well as through other brokers. The relation includes with the various consequences which create a pattern called patron-client